Deterioration laws of concrete durability under the coupling action of salt erosion and drying–wetting cycles - Chen, Shaojie; Ren, Jianxi; Ren, Xiang; Li, Yugen (Frontiers in Materials, 2022)
To investigate the deterioration laws of concrete durability under the coupling action of salt erosion and drying–wetting cycles, this study evaluated the macro–performance evolution of concrete under different environments (NaCl, Na2SO4, and MgSO4). Several measuring methods including nuclear magnetic resonance, computerized tomography tests, and microscopic morphology analysis are employed to investigate the damage mechanism of concrete. Experimental results show that with the action of salt erosion and drying–wetting cycles, the mass loss rate of concrete decreased first and then increased, and the relative dynamic modulus of elasticity and the compressive strength increased first and then decreased. The porosity and the pore quantity fluctuation increased. During the whole erosion process, needle-like attack products were formed in the pores, the crystals gradually filled the pores, and generated expansion pressure on the pore wall. As a result, concrete damage gradually occurred. Consequently, the damage degree was greater. The degrees of concrete damage under drying–wetting cycles induced were arranged as MgSO4>Na2SO4>NaCl.